Investigation on Microstructure of Potassium Nitrate/Sodium Nitrate Composites for Solar Storage System - Qianjun Mao; Ning Liu; Li Peng; Hongjun Wu (Advances in Materials Science and Engineering)
The performance of the material is determined by its structure, i.e., the composition of the material elements of the atomic structure, the molecular structure, and atoms or molecules in space arrangement and the aggregation characteristics. The microstructure of the material has important implications for the material performance. In this paper, five phase change materials, potassium nitrate, sodium nitrate, and the composites of KNO3-NaNO3/graphite (3%, 6%, and 9%), have been studied by the experiment, and the aim is to improve the storage performance of the solar storage system. The results show that potassium nitrate and sodium nitrate are significantly different in microstructure, that is, potassium nitrate is a layered structure and the sodium nitrate is a network structure. And, the graphite as additives can be physically combined with the molten salts, which leads to a different performance and distribution in the mixture. Therefore, it is an effective method in improving the performance of molten salts by using graphite as the supporting material. The results can provide a reference to future choose for solar storage materials.